JavaScript Language Design and Implementation in Tandem. - Ryu, Sukyoung; Park, Jihyeok (Communications of the ACM, 2024)
This article proposes utilization of mechanized specification in programming language development with JavaScript. The article details the history of JavaScript language specification and implementation of open source conformance testing showing how amendable JavaScript is to this new method. Topics include synthesis of conformance tests by JEST and the creation of JSAVER which allows for the generation of an automatic static analyzer of any version of ECMA-262, Javascript’s language specification.